Posterior Reversible Encephalopathy Syndrome Secondary to Mild Renal Artery Stenosis induced Hypertension in Child: A Case Report - Martelina, Yiska; Ananda Digdoyo; Wikrama, Ketut Wiswa (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2025)
Introduction: In addition to neurological symptoms such as impaired consciousness that can result in the rare incidence of a comatose state, seizures, and visual impairment, posterior reversible encephalopathy syndrome (PRES) is represented by a various type of non-specific symptoms such as headache, nausea, and vomiting. These clinical features are associated with distinctive imaging findings of vasogenic edema, primarily located in the bilateral posterior or parieto-occipital lobes, which is generally reversible. Case Report: We present here, a young 7-years-old girl, with a medical history of hypertension, sudden loss of consciousness lasting 1 minute, stereotypic seizures lasting 5 to 10 seconds with unknown etiology, had a history of blurred vision for approximately 24 hours after the seizures, multiple projectile vomiting, dizziness and altered mental status for 1 week. The characteristics of vasogenic edema observed in the bilateral parieto-occipital lobe, as seen in CT-scan imaging, along with the reversal of symptoms, contributed to the diagnosis of PRES in our patient. After the hypertension was treated and the symptoms were reversed, the patient was discharged in a stable condition. Conclusion: We report a case is a Posterior Reversible Encephalopathy Syndrome in young patient caused by hypertension and triggered by renal artery stenosis. Hypertension must be treated in patients with neurological symptoms like loss of consciousness, dizziness, and blurred vision. Suspicion of PRES must be considered a special case.